2016
DOI: 10.1007/s11274-016-2092-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the production of shikimic acid using the aroK knockout strain of Bacillus megaterium

Abstract: Shikimic acid has various pharmaceutical and industrial applications. It is the sole chemical building block for the antiviral drug oseltamivir (Tamiflu(®)) and one of the potent pharmaceutical intermediates with three chiral centres. Here we report a modified strain of Bacillus megaterium with aroK (shikimate kinase) knock out to block the aromatic biosynthetic pathway downstream of shikimic acid. Homologous recombination based gene disruption approach was used for generating aroK knock out mutant of B. megat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In another study, SA production in a mutant strain, obtained by inactivating the aroK gene via antisense RNA interference and gene deletion technology, was increased to 1850 mg/L, which is 2.69 times higher than that in E. coli DHPYA-T7 [ 37 ]. Similarly, the gene disruption method based on homologous recombination was performed to generate Bacillus megaterium ∆ aroK , and the SA yield in this strain, in a bioreactor (10L), was increased to 6 g/L, 12 times higher than that in wild-type strains [ 38 ]. Interestingly, Lee et al proposed a new way of not completely blocking the synthesis of aromatic amino acids, and significantly promoting the accumulation of SA.…”
Section: Sa Production By Metabolic Engineeringmentioning
confidence: 99%
“…In another study, SA production in a mutant strain, obtained by inactivating the aroK gene via antisense RNA interference and gene deletion technology, was increased to 1850 mg/L, which is 2.69 times higher than that in E. coli DHPYA-T7 [ 37 ]. Similarly, the gene disruption method based on homologous recombination was performed to generate Bacillus megaterium ∆ aroK , and the SA yield in this strain, in a bioreactor (10L), was increased to 6 g/L, 12 times higher than that in wild-type strains [ 38 ]. Interestingly, Lee et al proposed a new way of not completely blocking the synthesis of aromatic amino acids, and significantly promoting the accumulation of SA.…”
Section: Sa Production By Metabolic Engineeringmentioning
confidence: 99%
“…Bacillus subtilis , another microorganism generally recognized as safe, has been studied for production of shikimic acid. ,, However, 3-dehydroshikimic acid was always obtained as the major product, upon deactivation of pyruvate and shikimate kinases . Knockout of aroK in B. megaterium increased the production of shikimic acid by 6 times in flask culture when compared with the wild type . Fermentation of a different strain of the same bacterium allowed accumulation of shikimic acid in 12.5 g/L titer with fructose as the carbon source, which was obtained in 89% purity upon further purification of the fermentation broth .…”
Section: Synthesis Of Shikimic Acidmentioning
confidence: 84%
“…Knockout of aroK in B. megaterium increased the production of shikimic acid by 6 times in flask culture when compared with the wild type . Fermentation of a different strain of the same bacterium allowed accumulation of shikimic acid in 12.5 g/L titer with fructose as the carbon source, which was obtained in 89% purity upon further purification of the fermentation broth . Although fermentation of mutated strains of Citrobacter freundii resulted in production of shikimic acid in 10 g/L titer in flask culture, wild type strains isolated from soil were reported to provide the same compound in 22.3 g/L in a fed-batch bioreactor after culture conditions optimization. A process involving Gluconobacter oxidans growing cells, resting cells, dried cells, and cell membrane was reported to biotransform quinic acid to 3-dehydroshikimate .…”
Section: Synthesis Of Shikimic Acidmentioning
confidence: 99%
“…It is reported that a ∆aroK mutant of B . megaterium can promote shikimate production 41 . The aroK gene encodes shikimate kinase, which catalyzes the bioconversion of shikimate to shikimate-3-phosphate in an ATP-dependent phosphorylation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…8). By employing the experimental data reported in the literature 41 and also applying Eqs. (1) and (2), we ran 43 FBA simulations under the aforementioned conditions.…”
Section: Resultsmentioning
confidence: 99%